2020
DOI: 10.1126/sciadv.aaz1622
|View full text |Cite
|
Sign up to set email alerts
|

RALF1-FERONIA complex affects splicing dynamics to modulate stress responses and growth in plants

Abstract: The environmentally responsive signaling pathways that link global transcriptomic changes through alternative splicing (AS) to plant fitness remain unclear. Here, we found that the interaction of the extracellular rapid alkalinization FACTOR 1 (RALF1) peptide with its receptor FERONIA (FER) triggered a rapid and massive RNA AS response by interacting with and phosphorylating glycine-rich RNA binding protein7 (GRP7) to elevate GRP7 nuclear accumulation in Arabidopsis thaliana. FER-dependent GRP7 phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 51 publications
2
91
0
Order By: Relevance
“…Type 2C protein phosphatases indirectly inhibit OST1 activity via the dephosphorylation of its activation loop (Umezawa et al, 2009; Vlad et al, 2009) and ABA or osmotic stress activates SnRK2s. However, OST1 activity cannot be detected in higher‐order pp2c mutants under normal conditions (Brandt et al, 2015; Wang et al, 2018b), suggesting that OST1 activation requires additional proteins. An early study in the moss P. patens indicated that the ABA and abiotic stress‐responsive Raf‐like kinase (ARK), which belongs to the B3 group of Raf‐like MAPKKKs, participates in ABA and hyperosmotic stress signaling by regulating the activity of SnRK2s (Saruhashi et al, 2015).…”
Section: The Mapk Cascade In Drought Stressmentioning
confidence: 99%
“…Type 2C protein phosphatases indirectly inhibit OST1 activity via the dephosphorylation of its activation loop (Umezawa et al, 2009; Vlad et al, 2009) and ABA or osmotic stress activates SnRK2s. However, OST1 activity cannot be detected in higher‐order pp2c mutants under normal conditions (Brandt et al, 2015; Wang et al, 2018b), suggesting that OST1 activation requires additional proteins. An early study in the moss P. patens indicated that the ABA and abiotic stress‐responsive Raf‐like kinase (ARK), which belongs to the B3 group of Raf‐like MAPKKKs, participates in ABA and hyperosmotic stress signaling by regulating the activity of SnRK2s (Saruhashi et al, 2015).…”
Section: The Mapk Cascade In Drought Stressmentioning
confidence: 99%
“…Recently, the roles of Cr RLK1L proteins in regulating agronomic traits have begun to be appreciated in crop species ( Table 1 ). In general, Cr RLK1L proteins play versatile roles in plant growth and development, reproduction, hormone signaling, stress responses, immunity ( Escobar-Restrepo et al., 2007 ; Guo et al., 2009 , 2018 ; Duan et al., 2010 , 2014 ; Yu et al., 2012 , 2014 ; Haruta et al., 2014 ; Li et al., 2015 , 2016a ; Mao et al., 2015 ; Chen et al., 2016 ; Du et al., 2016 ; Ge et al., 2017 , 2019 ; Mecchia et al., 2017 ; Stegmann et al., 2017 ; Chakravorty et al., 2018 ; Feng et al., 2018 ; Franck et al., 2018 ; Gonneau et al., 2018 ; Hansen et al., 2019 ; Wang et al., 2020a ; Zhou and Zhang, 2020 ), energy production and RNA metabolism ( Xu et al., 2019 ; Zhu et al., 2020a ; Wang et al., 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…In the cytoplasm, the RALF1–FER complex also uses the small G-protein pathway to regulate auxin responses and root hair growth ( Duan et al., 2010 ) as well as abscisic acid (ABA) responses ( Yu et al., 2012 ; Chen et al., 2016 ). FER also monitors the carbon/nitrogen (C/N) balance by interacting with ATL6 ( Xu et al., 2019 ), regulates mRNA alternative splicing by phosphorylating the RNA-binding protein glycine-rich protein 7 (GRP7) to modulate plant fitness and flowering time ( Wang et al., 2020a , 2020b ) and promotes protein synthesis and polar cell growth by phosphorylating eIF4E1 ( Zhu et al., 2020a ). The RALF1–FER complex uses a “shortcut” mechanism to directly regulate gene expression by phosphorylating a DNA-binding protein, namely ErbB3-binding protein 1 (EBP1) ( Li et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was demonstrated that the interaction of FER with RALF1 resulted in the phosphorylation of the GLYCINE-RICH RNA-BINDING PROTEIN 7 (GRP7) to promote GRP7 nuclear accumulation, thus triggering a rapid and massive RNA alternative splicing response. GRP7 phosphorylation enhanced its mRNA binding ability and its association with the spliceosome component U1-70K, which depends on FER [ 68 ].…”
Section: Potential Functions Of Fer In Stress Tolerancementioning
confidence: 99%